A Rare Case of Basaloid Squamous Cell Carcinoma in the Genital Region - Fitria Puspita Dewi; Saputra, Arkan Runako (Universitas Ahmad Dahlan, 2024)
Vulvar carcinoma accounts for approximately 0,7% of all malignancies in females and 4% of cases of malignancies in the female reproductive organs. Basaloid squamous cell carcinoma (BSCC) is an uncommon squamous cell carcinoma (SCC) variant with aggressive biological features and frequent distant metastasis. BSCC is reported to occur in approximately 2% of cases in the head and neck region, such as the oral cavity, larynx, and hypopharynx, but can also be found in the nasopharynx and trachea. BSCC is rarely found in the female genital tract, only 6 cases of BSCC cancer in the genital tract have been reported. The detection of vulvar cancer often takes longer than necessary for several reasons. Firstly, the condition can be asymptomatic for a prolonged duration. Moreover, there is a lack of awareness among women about the disease and its signs, which further delays the diagnosis. This postponement in diagnosis results in a worse prognosis and fewer options for medical treatment, ultimately impacting women's psychosexual and psychosocial. We present the case of a 62-year-old woman who attended the obstetrics clinic of Dr. Sardjito Hospital with multiple blackish masses on the vulva extending to the gluteal region and also lymphadenopathy in the inguinal lymph nodes. A wide excision vulvectomy was performed, and the specimen was sent to the Anatomical Pathology Laboratory.